DEVELOPMENT AND VALIDATION OF UV-VISIBLE SPECTROPHOTOMETRIC METHOD FOR ANALYSIS OF BOSENTAN IN SPIKED HUMAN PLASMA - K. , BHAVYA SRI; H. , MOUNIKA C. (International Journal of Current Pharmaceutical Research, 2019)
Objective: The aim of the present study is to develop and validate a simple, efficient, economical and accurate UV-visible spectrophotometric method for estimation of bosentan in spiked human plasma. Methods: The analyte was extracted by Liquid-liquid Extraction (LLE) procedure using acetonitrile and chloroform. Absorbance of the analyte in the extract was measured at 270 nm using ethanol as a diluent. The developed method was validated for linearity, accuracy and robustness. Results: The proposed method was found to be linear in the range of 6 to 18 mg/ml. The correlation coefficient (r2) was found to be 0.99. The results revealed that the linearity, accuracy and robustness of the developed method were within the acceptable range. Conclusion: The analytical technique presented here demonstrates shorter and easier sample preparation method, decreased analysis time and reduces the need for complicated or expensive equipment. The sample preparation method used in this study can also be further extended to higherend analytical techniques and other biological samples for quantification of bosentan.